Central obesity, smoking habit, and hypertension are associated with lower antibody titres in response to COVID‐19 mRNA vaccine. Issue 1 (11th May 2021) - Watanabe, Mikiko; Balena, Angela; Tuccinardi, Dario; Tozzi, Rossella; Risi, Renata; Masi, Davide; Caputi, Alessandra; Rossetti, Rebecca; Spoltore, Maria Elena; Filippi, Valeria; Gangitano, Elena; Manfrini, Silvia; et al.
Abstract: Aims: To explore variables associated with the serological response following COVID‐19 mRNA vaccine. Methods: Eighty‐six healthcare workers adhering to the vaccination campaign against COVID‐19 were enrolled in January–February 2021. All subjects underwent two COVID‐19 mRNA vaccine inoculations (Pfizer/BioNTech) separated by 3 weeks. Blood samples were collected before the 1st and 1–4 weeks after the second inoculation. Clinical history, demographics, and vaccine side effects were recorded. Baseline anthropometric parameters were measured, and body composition was performed through dual‐energy‐X‐ray absorptiometry. Results: Higher waist circumference was associated with lower antibody (Ab) titres ( R = −0.324, p = 0.004); smokers had lower levels compared to non‐smokers [1099 (1350) vs. 1921 (1375), p = 0.007], as well as hypertensive versus normotensive [650 ± 1192 vs. 1911 (1364), p = 0.001] and dyslipideamic compared to those with normal serum lipids [534 (972) vs 1872 (1406), p = 0.005]. Multivariate analysis showed that higher waist circumference, smoking, hypertension, and longer time elapsed since second vaccine inoculation were associated with lower Ab titres, independent of BMI, age. and gender. Conclusions: Central obesity, hypertension, and smoking are associated with lower Ab titres following COVID‐19 vaccination. Although it is currently impossible to determine whether lower SARS‐CoV‐2 Abs lead to higher likelihood of developing COVID‐19, it is well‐established that neutralizing antibodies correlate with protection against several viruses including SARS‐CoV‐2. Our findings, therefore, call for a vigilant approach, as subjects with central obesity, hypertension, and smoking could benefit from earlier vaccine boosters or different vaccine schedules.